Dinamika Pemidanaan Khalwat di Aceh: Urgensi Revisi Qanun Jinayat untuk Mencegah Konflik Hukum - Azharuddin, Azharuddin; Masyitha, Siti; Tia, Novianti Indah; Oktizanna, Wulan; Maghfirah, Siti (El-Suffah: Jurnal Studi Islam, 2024)
This research explores and analyzes the problems that arose in connection with the problematic rule of law in Aceh, specifically when the Aceh Governor Circular Letter Number 451/11286 was issued with the Aceh Qanun Jinayat, especially in Article 12 Paragraph (1) regarding khalwat. Basically, the qanun limits the meaning of khalwat in the field of work or in public places, while the Aceh Governor's SE wants khalwat acts to continue to be enforced even if they are carried out in public places. This research aims to identify tensions or conflicts that may arise between the provisions of the Qanun and the Governor's SE and their impact on the implementation and understanding of the law later, because these two regulations provide opportunities in terms of legal interpretation and even practical implementation. This research uses normative juridical research methods because it only discusses issues of legal rules, specifically in Qanun Article 12 paragraph (1) Qanun Jinayat Aceh with Governor's Decree Number 451/11286. The results of the research show that there are fundamental differences regarding the criminalization of khalwat in the Aceh Qanun Jinayat and the Aceh Governor's SE, this could lead to legal conflicts in the future due to legal interpretation by certain parties. The legal dynamics in Aceh regarding khalwat must be addressed as soon as possible before a legal conflict occurs later, by revising the meaning of khalwat and it must be adapted to the social and religious conditions of the Acehnese people Keywords: Problematic, Legal Rules, Khalwat.  Abstrak: Sehubungan dengan problematika aturan hukum di Aceh, tepatnya ketika terbitnya Surat Edaran Gubernur Aceh Nomor 451/11286 dengan Qanun Jinayat Aceh khususnya dalam Pasal 12 Ayat (1) terkait khalwat. Pada dasarnya qanun membatasi makna khalwat dalam bidang pekerjaan atau di tempat umum, sedangkan SE Gubernur Aceh menginginkan perbuatan khalwat tetap diberlakukan walau dilakukan di tempat publik. Penelitian ini bertujuan untuk mengidentifikasi ketegangan atau konflik yang mungkin timbul antara ketentuan Qanun dan SE Gubernur serta dampaknya pada pelaksanaan dan pemahaman hukum nantinya, sebab kedua aturan tersebut memberi peluang dalam hal interpretasi hukum bahkan sampai dalam pelaksanaan praktis. Penelitian ini menggunakan metode penelitian yuridis normatif karena hanya membahas permasalahan aturan hukum semata, tepatnya dalam qanun Pasal 12 ayat (1) Qanun Jinayat Aceh dengan SE Gubernur Nomor 451/11286. Hasil penelitian menunjukkan bahwa terjadinya perbedaan mendasar terkait pemidanaan khalwat yang ada dalam Qanun Jinayat Aceh dengan SE Gubernur Aceh, hal ini bisa menimbulkan konflik hukum ke depannya akibat terjadinya penafsiran hukum oleh pihak-pihak tertentu. Dinamika hukum  di Aceh terkait khalwat ini sesegera mungkin harus ditangani sebelum terjadi konflik hukum nantinya, dengan cara merevisi ulang terkait makna khalwat dan harus disesuaikan dengan kondisi sosial dan keagamaan masyarakat Aceh.